2022
DOI: 10.1186/s43141-022-00440-2
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of chemical profiles and molecular targets of Mondia whitei leave fractions bioactive as novel therapeutics: an in vitro and in silico assay

Abstract: Background Mondia whitei root is often used in Africa as a local therapeutic agent for libido enhancement. The fractions of the M. whitei leaves (MWL) lack chemical characterization of their bioactive components and possible molecular targets. We characterized and investigated its molecular target as therapeutic agents in an in vitro and in silico assay. Mineral compositions, antioxidant, and GC-MS characterization were studied. The cytotoxicity effect was measured on HeLa and HT-29 cells by MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…This was consistent with results from studies conducted by [17][18][19] which reported the presence of alkaloids, avonoids, terpenoids, and glycosides in lemon extracts but negative for tannins. Furthermore, [20][21][22] identi ed all the phytochemicals detected in the MCERBE by this study in addition to other phytochemical. The observed differences in the phytochemicals may be attributed to differences in environmental conditions in the different geographical regions.…”
Section: Discussionmentioning
confidence: 68%
“…This was consistent with results from studies conducted by [17][18][19] which reported the presence of alkaloids, avonoids, terpenoids, and glycosides in lemon extracts but negative for tannins. Furthermore, [20][21][22] identi ed all the phytochemicals detected in the MCERBE by this study in addition to other phytochemical. The observed differences in the phytochemicals may be attributed to differences in environmental conditions in the different geographical regions.…”
Section: Discussionmentioning
confidence: 68%
“…which have been reported to be cytotoxic to brine shrimp, human colorectal adenocarcinoma (HT-29) and cervical cancer (HeLa) cell lines and human epidermoid larynx carcinoma cancer (Hep 2) respectively support the antiproliferative activity being observed in M. guineensis . 17,18,19 Toxicity assay of Motandra guineensis extract and fractions Table 2 shows the results of toxicity testing on green monkey Vero cells as a measure of safety. Crude ethanol extract and fractions were less toxic in Vero cells than the standard drug, Tamoxifen.…”
Section: Antiproliferative Assay Of Motandra Guineensis Extract and F...mentioning
confidence: 99%
“…12,13 Oxidative stress is an imbalance between the cellular production of ROS and the counteracting antioxidant mechanisms, which leads to the damage of cellular macromolecules. 14 The ROS generated in oxidative stress following alcohol intake include abnormal malondialdehyde (MDA), 8-F2-isoprostane (8-iso-PGF2α) levels, protein carbonyl (PC), 8-hydroxy-2-deoxyguanosine (8-OHdG) and 8-oxo-7, 8-dihydroguanosine (8-oxoGuo). 15,16 Oxidative stress activates the immune-inflammatory pathways where pro-inflammatory cytokines are released.…”
Section: Introductionmentioning
confidence: 99%